Hepatoprotective Effects of a Ruthenium(II) Schiff Base Complex in Rats with Diet-Induced Prediabetes - Lindokuhle Patience Mabuza; Mlindeli Wilkinson Gamede; Sanam Maikoo; Irvin Noel Booysen, PhD; Phikelelani Siphosethu Nguban, PhD; Andile Khathi, PhD (Elsevier, 2019)
ABSTRACT: Background: Progressive insulin resistance in a prediabetic state has been reported to be the predominant causative factor for the development of nonalcoholic fatty liver disease. The combination of dietary modification and pharmacotherapy has been recommended to manage diabetic liver complications. However, poor patient compliance and toxicity of current drug therapy on liver function still results; thus, newer alternative drugs are required. Objective: This study sought to investigate the hepatoprotective effects of the ruthenium(II) Schiff base complex in the presence and absence of dietary intervention in a diet-induced pre-diabetic rat model. Methods: Prediabetic rats were randomly allocated to respective treatment groups. The ruthenium-based compound (15 mg/kg) was administered to the prediabetic rats in both the presence and absence of dietary intervention once a day every third day for 12 weeks. Results: The administration of the ruthenium compound in both the presence and absence of dietary intervention resulted in the restoration of liver and body weights. This treatment also reduced liver damage enzyme biomarkers, bilirubin, and sterol regulatory element binding protein 1c concentrations in the plasma. Conclusions: The ruthenium(II) complex showed beneficial effects as it ameliorated and prevented the progression of diabetes-related liver derangements while eliminating the hepatotoxicity associated with the use of metal compounds. However, further studies are still required to further determine the physiological mechanisms behind this effect. Key words: Dietary intervention, Hepatic insulin resistance, Nonalcoholic fatty liver disease, Prediabetes, Ruthenium(II) complex